Pricing of bond options in India. (3rd October 2022) - Chaudhuri, Sunrita; Pandey, Alok
Bond options are widely used for managing interest rate risks. Bond options were introduced in India in December 2019. Various bond option pricing models are used by practitioners in the market. This study prices a European call option on 10-Year G-Sec using three models, the Jamshidian's option pricing formula based on Vasicek's model, the Black's option pricing model and Black, Derman and Toy's no arbitrage model. The results show that the option prices are different for different models. The study concludes that volatility of interest rates is an important consideration in each of the models and needs to be standardised to get comparable results.